Pengaruh tingkat kepadatan tanaman terhadap pertumbuhan Sorgum Brown Mid Rib (BMR) yang diberi pupuk bokashi kotoran ayam pada kondisi ternaung - Lundeto, S.W.; Anis, S.D.; Kaunang, W.B.; Sumolang, C.I.J. (Universitas Sam Ratulangi, 2021)
THE IMPACT OF PLANT’S DENSITY ON THE GROWTH OF SORGHUM BROWN MID RIB WITH CHICKEN MANURE FERTILIZER IN AN ELEVATED STATE. The purpose of this research was determines growth of sorghum BMR with different population density use chicken manure fertilizer in an elevated state. This experiment was conducted using Completely Randomized Design (CRD). The treatment consisted of four planting density, (P1=(1 plant/Polybag) P2=(2 plants/polybag) P3=(3 plants/polybag) P4=(4 plants/polibag), each treatment had seven replications. Data were analyzed using analysis of variance and HSD test. The variables measured were growth that are plant’s height, leaf length, and number of leaves. The results showed that different planting population were significant different (P<0.01) on plant’s height, leaf length, and number of leaves. HSD test showed that planting population P1=(1 plant/Polybag) were significant (P<0.01) have higher plant’s height, leaf length, and number of leaves than P3=(3 plants/polybag) and P4=(4 plants/polybag). It can be concluded that planting density P1=(1 plant/Polybag) have the highest growth of sorghum BMR that were highest plant’s height, leaf length, and number of leaves.